Implementation of adolescent HIV screening in two urban pediatric emergency departments in the United States - Wei Li A. Koay; Kavitha Ganesan; Justin Unternaher; Sephora Morrison; Shilpa J. Patel; Monika Goyal; Natella Rakhmanina (PLoS ONE, 2025)
Objectives Routine, opt-out HIV screening of adolescents and youth (AY) is recommended in the United States in all healthcare settings, including emergency departments (EDs), however, data on ED-based HIV screening among AY remains limited. We aimed to describe the implementation and outcomes of a routine HIV AY screening program in two pediatric EDs in Washington, DC. Methods This was a cross-sectional prospective study of an opt-out HIV point-of-care testing (POCT) program of AY aged 13–24 years at a tertiary-based pediatric ED and community-based pediatric ED in Washington DC from March 2009 to February 2019. Descriptive statistics were used to analyze annual program performance by numbers of eligible AY seen, approached, tested, and new HIV identified. One-time ED staff survey collected barriers to HIV screening. Results During the 10-year period, out of 191,107 AY seen in ED, 21.9% (n=41,913) were approached for HIV POCT, of which 58.7% were tested (n=24,599); 23 new HIV infections (0.09% of tested AY) were identified. A higher proportion of AY were approached at the community-based ED compared to the tertiary-based ED (58.5% vs. 11.4%). The tertiary-based ED experienced a decline in AY approached after shifting the task from designated testers to ED staff. Among 179 surveyed ED staff, the most common barriers to HIV POCT included forgetting to offer the test (41.9%), lack of time (33.0%) and discomfort when approaching parents/guardians (15.6%). Conclusions The rate of new HIV diagnoses among screened AY ED patients was <0.1%, however, less than one-quarter of eligible AY were approached for testing. The staff-run HIV POCT model was successful in the lower acuity community-based pediatric ED, while the larger tertiary-based pediatric ED performed well only with the support of dedicated testers. Future studies are necessary to identify the optimal implementation strategy for sustainable ED-based AY HIV screening in the US.